Economic Effects of Tightening Accounting Standards to Restrict Earnings Management - Ewert, Ralf; Wagenhofer, Alfred (The Accounting Review, 2005)
This paper examines the usual claim that tighter accounting standards reduce earnings management and provide more relevant information to the capital market. We distinguish between accounting and real earnings management and assume that a standard setter can only influence accounting earnings management by the tightness of standards. In a rational expectations equilibrium model, we find that earnings quality increases with tighter standards, but we identify several consequences that may outweigh this benefit. First, managers increase costly real earnings management because the higher earnings quality increases the marginal benefit of real earnings management. Second, tighter standards can increase rather than decrease expected accounting and total earnings management. Third, the expected total costs of earnings management can also increase. We provide conditions for the occurrence of each of these effects.